STRATEGI CORPORATE COMMUNICATION PT GARUDA INDONESIA DALAM MEMPERTAHANKAN CITRA GARUDA INDONESIA SEBAGAI MASKAPAI TERBAIK DI ASIA TAHUN 2013-2014 - Ayu, Monalisa; Alit Suryawati, I Gusti; Dewi Pascarani, Ni Nyoman (E-Jurnal Medium, 2016)
ABSTRACT Communication becomes an important in building an organization or company in order to produce the positive image in the public mind. It is highly considered by the Corporate Communications Division from PT. Garuda Indonesia in maintaining image credibility that formed long ago in the community. The company that engaged in the field of aviation services has been named as the best airline in Asia by APEX (Airline Passenger Experience Association) for two consecutive years since 2013 and it surpass four other airlines such as Singapore Airlines, Cathay Pacific, Korean Air, and EVA. The purpose of this research is to find out the strategy of Corporate Communication Division of PT. Garuda Indonesia in maintaining the image as the best company in Asia among 2013-2014. This research uses the descriptive-qualitative method. The results of this research is to indicate that the strategy done by the Corporate Communications Division of PT. Garuda Indonesia is started by determining the company’s object first. Afterwards, the company empowers three big potential of resources in order to obtain the company purposes. Then, the purpose of the company is communicated to all of the public by the official site of Garuda Indonesia and holds the Focus Group Discussion (FGD) activity with the crew of media. The last step is to hold the “door to door” activity or the spreading of the satisfaction marking form to all prime public of Garuda Indonesia in the end of the year as the evaluation form of the Corporate Communication strategy applied during this time. Keywords: Strategy, Corporate Communication, Image, Garuda Indonesia